Determinants of Brachial-Ankle Pulse Wave Velocity in Chinese Patients with Rheumatoid Arthritis - Ping Li; Cheng-xun Han; Cui-li Ma; Jia-long Guo; Bo Liu; Juan Du; Li-qi Bi (Clinical and Developmental Immunology)
Objective. To investigate the relationship between Brachial-ankle pulse wave velocity (baPWV), and its associated risk factors in Chinese patients with RA. Methods. 138 Chinese RA patients and 150 healthy subjects were included. baPWV of all the participants was measured. RA related factors were determined, as well as traditional cardiovascular risk factors. Results. baPWV was significant higher in RA group (1705.44 ± 429.20 cm/s) compared to the healthy control group (1386.23 ± 411.09 cm/s) (P<0.001). Compared with low baPWV group, high baPWV group patients were significantly older (P = 0.008) and taller (P = 0.033). Serum cholesterol (P = 0.035), triglycerides (P = 0.004), and LDL level (P = 0.006) were significantly higher in high baPWV group patients compared with low baPWV group patients. The baPWV of RA patients was positively correlated with age (r = 0.439, P<0.001), and serum cholesterol level (r = 0.231, P = 0.035), serum triglycerides level (r = 0.293, P<0.001), serum LDL level (r = 0.323, P = 0.003). Meanwhile, baPWV negatively correlated with the height of RA patients (r = −0.253, P = 0.043). Multivariate regression analysis showed that baPWV of RA group was independently associated with age and serum triglycerides level. Conclusions. The old age and high level of serum triglycerides may be the major determinants of arterial stiffness in Chinese RA patients.